Dental caries experience, oral health status and treatment needs of dental patients with autism - Mohamed Abdullah Jaber (University of São Paulo, 2011)
OBJECTIVES: Autism is a lifelong neurodevelopmental disorder. The aims of this study were to investigate whether children with autism have higher caries prevalence, higher periodontal problems, or more treatment needs than children of a control group of non-autistic patients, and to provide baseline data to enable comparison and future planning of dental services to autistic children. MATERIAL AND METHODS: 61 patients with autism aged 6-16 years (45 males and 16 females) attending Dubai and Sharjah Autism Centers were selected for the study. The control group consisted of 61 non-autistic patients chosen from relatives or friends of autistic patients in an attempt to have matched age, sex and socioeconomic status. Each patient received a complete oral and periodontal examination, assessment of caries prevalence, and caries severity. Other conditions assessed were dental plaque, gingivitis, restorations and treatment needs. Chi-square and Fisher's exact test of significance were used to compare groups. RESULTS: The autism group had a male-to-female ratio of 2.8:1. Compared to controls, children with autism had significantly higher decayed, missing or filled teeth than unaffected patients and significantly needed more restorative dental treatment. The restorative index (RI) and Met Need Index (MNI) for the autistic children were 0.02 and 0.3, respectively. The majority of the autistic children either having poor 59.0% (36/61) or fair 37.8% (23/61) oral hygiene compared with healthy control subjects. Likewise, 97.0% (59/61) of the autistic children had gingivitis. CONCLUSIONS: Children with autism exhibited a higher caries prevalence, poor oral hygiene and extensive unmet needs for dental treatment than non-autistic healthy control group. Thus oral health program that emphasizes prevention should be considered of particular importance for children and young people with autism.